Cmentarzysko ciałopalne kultury łużyckiej w Wierzbowej, stanowisko 1, gm. Wartkowice, w świetle analiz antropologicznych i archeologicznych - Zielińska, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Osseous material coming from a cremation cemetery of the Lusatian culture population in Wierzbowa was subjected to anthropological analyses. 84 out of 92 uncovered grave units were analysed. 97 identified burials included osseous remains of 101 individuals among which 36 males, 19 females, 21 children, 25 individuals of undefined sex, and 11 individuals of undefined sex and age were distinguished. In case of 16 individuals their height was defined. In the examined population an average age of death was 35 years for men and 29 years for women. Distribution of elements in grave deposits allowed to state the presence of clay rattles in the burials depositing remains of children. The use of a macroscopic method allowed to observe pathological changes in bone systems. Among them dominate diseases caused by overstraining of organism and ageing process. Considerable amount of diseases constitute systemic illnesses, particularly hypertrophic changes in eye sockets in case of children. Besides, cases of developmental anomalies and illnesses of masticatory system were observed. Analysis of the results of examinations concerning biological state and pathological changes suggests hard living conditions of the population.